A Functional Transient Receptor Potential Vanilloid 4 (TRPV4) Channel Is Expressed in Human Endothelial Progenitor Cells. Issue 1 (January 2015) - Dragoni, Silvia; Guerra, Germano; Pla, Alessandra Fiorio; Bertoni, Giuseppe; Rappa, Alessandra; Poletto, Valentina; Bottino, Cinzia; Aronica, Adele; Lodola, Francesco; Cinelli, Maria Pia; Laforenza, Umberto; Rosti, Vittorio; et al.
<x xml:space="preserve">Abstract</x> Endothelial progenitor cells (EPCs) are mobilized into circulation to replace damaged endothelial cells and recapitulate the vascular network of injured tissues. Intracellular Ca2+ signals are key to EPC activation, but it is yet to be elucidated whether they are endowed with the same blend of Ca2+‐permeable channels expressed by mature endothelial cells. For instance, endothelial colony forming cells (ECFCs), the only EPC subset truly committed to acquire a mature endothelial phenotype, lack canonical transient receptor potential channels 3, 5 and 6 (TRPC3, 5 and 6), which are widely distributed in vascular endothelium; on the other hand, they express a functional store‐operated Ca2+ entry (SOCE). The present study was undertaken to assess whether human circulating EPCs possess TRP vanilloid channel 4 (TRPV4), which plays a master signalling role in mature endothelium, by controlling both vascular remodelling and arterial pressure. We found that EPCs express both TRPV4 mRNA and protein. Moreover, both GSK1016790A (GSK) and phorbol myristate acetate and, two widely employed TRPV4 agonists, induced intracellular Ca2+ signals uniquely in presence of extracellular Ca2+. GSK‐ and PMA‐induced Ca2+ elevations were inhibited by RN‐1734 and ruthenium red, which selectively target TRPV4 in mature endothelium. However, TRPV4 stimulation with GSK did not cause EPC proliferation, while the pharmacological blockade of TRPV4 only modestly affected EPC growth in the presence of a growth factor‐enriched culture medium. Conversely, SOCE inhibition with BTP‐2, La3+ and Gd3+ dramatically decreased cell proliferation. These data indicate that human circulating EPCs possess a functional TRPV4 protein before their engraftment into nascent vessels. J. Cell. Physiol. 229: 95–104, 2014. © 2014 Wiley Periodicals, Inc.